E0317 Comparative effectiveness of renin angiotensin system blockades plus CCBs or diuretics for essential hypertension a systematic review. (17th November 2010) - Ruixin, Ma; Jing, Yu; Dian, Xu; Longquan, Yang; Peijun, Liu; Feng, Bai
Abstract : Backround: The relative effectiveness of two combination therapy- Renin Angiotensin System (RAS) blockades/calcium channel blockers (CCBs) versus RAS blockades/diuretics for lowering blood pressure is unknown. This systematic review is to compare the benefits and harms of RAS blockades plus CCBs versus RAS blockades plus diuretics for treating essential hypertension in adults. Methods: We retrieved MEDLINE, the Cochrane Central Register of Controlled Trials, EMBASE and SCI using computer to identify relevant randomised controlled trials in English that directly compared the effect of RAS blockades plus CCBs with that of RAS blockades plus diuretics in adult patients with essential hypertension, reported an outcome of mean difference of BP reduction or interest, lasted at least 4 weeks, and included at least 20 patients. A standardised protocol with predefined criteria was used to extract data on study design, interventions, population characteristics, and outcomes; We evaluated study quality and applicability; and assessed the strength of the evidence for key outcomes. Results: Five clinical studies were eventually included. We found no significant difference between RAS blockades/CCBs with RAS blockades/diuretics in reduction of blood pressure. However, RAS blockade/CCBs associated with significant stronger DBP response rate. No differential effects were observed for the incidence of adverse events. Conclusion: Available evidence shows that RAS blockade/CCBs and blockade/diuretics have similar effects on blood pressure control. High strength of evidence is needed. Data regarding is patient subgroups were missing.